2000
DOI: 10.1093/jn/130.4.767
|View full text |Cite
|
Sign up to set email alerts
|

Plant Stanol Esters Affect Serum Cholesterol Concentrations of Hypercholesterolemic Men and Women in a Dose-dependent Manner

Abstract: The effect of plant stanol ester on serum cholesterol is dose-dependent. However, it is not clear what the dose is beyond which no additional benefit can be obtained. Therefore, we determined the dose-response relationship for serum cholesterol with different doses of plant stanol ester in hypercholesterolemic subjects. In a single-blind design each of 22 men or women consumed five different doses of plant stanol [target (actual) intake 0 (0), 0.8 (0.8), 1.6 (1.6), 2.4 (2.3), 3.2 (3.0) g/d] added as plant stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
92
5
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(116 citation statements)
references
References 30 publications
11
92
5
8
Order By: Relevance
“…These symptoms were similar to those found in earlier studies (Hallikainen et al, 2000b;Neil et al, 2001) and occurred occasionally in both groups. As in earlier studies (Gylling et al, , 1999Miettinen et al, 1995;Mensink et al, 2002), no serious adverse effects were reported.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These symptoms were similar to those found in earlier studies (Hallikainen et al, 2000b;Neil et al, 2001) and occurred occasionally in both groups. As in earlier studies (Gylling et al, , 1999Miettinen et al, 1995;Mensink et al, 2002), no serious adverse effects were reported.…”
Section: Discussionsupporting
confidence: 91%
“…In earlier studies, serum apo B concentration has decreased significantly after the use of plant stanols (Gylling and Miettinen, 1994;Hallikainen et al, 2000b;Homma et al, Weeks LDL cholesterol (mmol/l) 2. Baseline cholesterol and apo B levels were defined as the mean of the values measured at weeks -1 and 0.…”
Section: Discussionmentioning
confidence: 91%
“…Consumption of plant sterol esters-enriched spread appeared to have no adverse side effects, defined as reported adverse events or undesirable changes in clinical chemical parameters, hematological parameters and urinalysis. The absence of side effects is in agreement with the observations in earlier, shorter-term, clinical and safety studies (Hendriks et al, 1999;Weststrate & Meijer, 1998;Baker et al, 1999;Hepburn et al, 1999;Waalkens-Berendsen et al, 1999;Weststrate et al, 1999;Ayesh et al, 1999;Sanders et al, 2000;Miettinen et al, 1995;Hallikainen et al, , 2000a Safety of plant sterol esters-enriched spread HFJ Hendriks et al 1999; Denke, 1995, Jones et al, 2000Sierksma et al, 1999;Tammi et al, 2000;Vuorio et al, 2000;Nguyen et al, 1999;Blair et al, 2000). Plant sterols are slightly absorbed ( < 5%) and could subsequently be exchanged with cholesterol in an equilibrium fashion in various sterol pools, including cell membranes.…”
Section: Discussionsupporting
confidence: 81%
“…Efficacy may depend on many different factors like intake level (Hendriks et al, 1999;Hallikainen et al, 2000a), background diet (Hallikainen et al, 2000b;Denke, 1995), composition of the sterol mixture (Jones et al, 2000;Sierksma et al, 1999) and specific characteristics of the subjects studied Tammi et al, 2000;Vuorio et al, 2000), like genetic background, compliance and eating moment. Mietinen et al (1995) reported a slightly higher efficacy, most likely due to the larger intake of plant stanols as compared with the plant sterol intake in the trial reported here (2.6 g stanols vs 1.6 g sterols per day).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation